Expression of herpesvirus in adherent cells derived from bone marrow of latently infected guinea pigs. - Gonzalez-Serva, A. (1978)
The role of bone marrow adherent cells in the latency of guinea pig herpes-like virus (GPHLV) was explored. Cultures of macrophage-enriched adherent cells derived from infected guinea pigs were examined for evidence of latent GPHLV infection. Expression of the virus was detected in these cultures 9 to 10 days after in vitro cultivation. Increasing virus infectivity titers as well as light and electron microscopic evidence of virion assembly in macrophages and fibroblasts were demonstrated. Infections virus was detected in the bone marrow adherent cells that had attached for 30 or 120 minutes but only following reverse cocultivation. The data showed not only that the bone marrow adherent cells were susceptible to GPHLV in vitro but also that GPHLV was harbored by the macrophage-enriched bone marrow population in vivo in latently infected guinea pigs.